Aadhar Data Collection Android Application Using Google Firebase Database Technology - Prakash Patidar, Chandra (International Journal of Computer Sciences and Engineering, 2022)
As the name Aadhar Data Collection Android Application suggests, this document provides detailed information about the Aadhar Data Collection Android Application (District Aadhar Data Collection Application (Dhar)), the data collected from users and managed by the administrator of the application. The industry of mobile application is growing rapidly with the new mobile technologies. Which was composed of multiple operating systems such as Symbian OS, Android OS, iOS and Blackberry etc are considered to be the most widely used operating systems and are user friendly mobile platform.